Using of Essential Oil Mixture in Quail Breeders (Coturnix Coturnix Japonica) for Improving Cecal Short-Chain Fatty Acid Concentrations - Özlem Durna Aydın; Gültekin Yıldız (Turkish Journal of Agriculture: Food Science and Technology)
The aim of this study is to investigate the effect of added to mixture essential oil consist of mint oil, juniper oil, rosemary oil and oregano vulgare oil added in drinking water at on intestinal health in quail breeders. A total of 160 Japanese quail breeders (control group each subgroup 6 females 6 males, experimental groups each subgroup 5 females 5 males) 17 weeks of age were randomly divided into 3 treatment groups and each group was divided into 5 replicates. The experimental period lasted 56 days. Maize and soybean meal-based diets were offered ad libitium to the birds from during the experimental period. Treatments were as follows: C, (Control; without supplementation to the drinking water); E1 (0,1ml/L essential oil mixture supplementation to the drinking water) and E2 (0,3ml/L essential oil mixture supplementation to the drinking water. Acetic acid, butyric acid, isocaproic acid and SCFA values were linearly affected by the increasing level of essential oil mixture (mint oil, juniper oil, rosemary oil and oregano vulgare oil). There were no significant differences in propionic acid, isobutyric acid, valeric acid, isovaleric acid, caproic acid and BCFA concentrations. In conclusion, essential oil mixture consists of mint oil, juniper oil, rosemary oil and oregano vulgare oil can be used to improve intestinal health in quail breeders drinking water.